Sikap Petani Padi Terhadap Program Pupuk Bersubsidi di Desa Caturharjo Kecamatan Pandak Kabupaten Bantul - Triyono, Triyono; Rifa’i, Afrizal (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The subsidized fertilizer program is a distribution program implemented by the government to help farmers meet farmers' fertilizer needs in rice cultivation. This study aims to, describe the profile of rice farmers, describe the attitude of rice farmers towards the subsidized fertilizer program, describe the factors that correlate with the attitude of farmers to the subsidized fertilizer program. The method used in this study used descriptive analysis. Data collection was carried out by direct interviews with farmers using questionnaire guides. The results showed that the average age of rice farmers in Caturharjo Village had an age range of 56-65 years, and the average education taken at the elementary school level. Rice farmers in Caturharjo Village have experience in farming with a range of 36-50 years, the average area of farmer's arable land is 1,463.33 m2, with the status of ownership of arable land, namely rent. The net income of rice farmers in one planting season is Rp1,000,000-3,000,000, and the number of family members is 3-4 people. The attitude of rice farmers towards the subsidized fertilizer program is included in the good category. Factors correlated with farmers' attitudes to subsidized fertilizer programs. The value of the correlation coefficient was very weak in the variables age (-0.011), education level (0.015), and land area (-0.245) with farmers' attitudes towards subsidized fertilizer programs, while for experience variables (-0.157) had a weak relationship strength with farmers' attitudes towards subsidized fertilizer programs.